Hedging, ambiguity, and the reversal of order axiom [dataset] - Oechssler, Joerg; Rau, Hannes; Roomets, Alex (Universität, 2019)
We ran experiments that gave subjects a straight-forward and simple opportunity to hedge away ambiguity in an Ellsberg-style experiment. Subjects h...
Deposit date: 2019-08-29
Gesehen am 02.09.2019
Keywords: Forschungsdaten; Datenbank